2013
DOI: 10.1371/journal.pntd.0002416
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Filariasis in Nigeria; Micro-stratification Overlap Mapping (MOM) as a Prerequisite for Cost-Effective Resource Utilization in Control and Surveillance

Abstract: BackgroundNigeria has a significant burden of lymphatic filariasis (LF) caused by the parasite Wuchereria bancrofti. A major concern to the expansion of the LF elimination programme is the risk of serious adverse events (SAEs) associated with the use of ivermectin in areas co-endemic with Loa filariasis. To better understand this, as well as other factors that may impact on LF elimination, we used Micro-stratification Overlap Mapping (MOM) to highlight the distribution and potential impact of multiple disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 41 publications
1
53
1
Order By: Relevance
“…Evidence from research shows that, in 2013, 34 African countries were endemic to lymphatic filariasis, and Nigeria had the highest burden, with 80 to 120 million people at risk [7,8]. In 2015, Nigeria contributed the highest burden (29 million) of schistosomiasis in SSA [9].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence from research shows that, in 2013, 34 African countries were endemic to lymphatic filariasis, and Nigeria had the highest burden, with 80 to 120 million people at risk [7,8]. In 2015, Nigeria contributed the highest burden (29 million) of schistosomiasis in SSA [9].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Participants expressed optimism about the feasibility of these potential solutions leveraging on the following enabling factors: (1) existing relationships and linkage with the Health Policy Research Group; (2) improved individual competence and organisational capacity for EIDM; (3) good political will and commitment to health sector improvements by the current State governor; (4) increasing interest to integrate research evidence in decision-making processes among users and producers of evidence; (5) active engagement of decision-makers in the Ministry of Economic Planning and Budgeting to facilitate the release of budgetary allocations to health; (6) availability of donors/partners in NTDs and malaria control in the State, (e.g. The Carter Center in collaboration with Research Triangle Institute, GOWON Foundation, WHO, UNICEF); and (7) willingness to create a knowledge translation forum between users and producers of evidence.…”
Section: Current Enablers To Potential Solutionsmentioning
confidence: 99%
“…Whilst the resulting map delineates environmental suitability for LF transmission, it may include areas where transmission does not actually occur, due either to the disease never having been imported into the area or the consequence of control leading to local elimination. To reflect this, we masked the environmental distribution map to remove areas which are known to be currently non-endemic according to WHO [39,100,101] and other sources [20,40,41,44,99]. Non-endemicity was considered when no cases had been reported for the last 10 years and transmission assessment surveys confirmed the interruption of LF transmission.…”
Section: Defining Limits Of Transmissionmentioning
confidence: 99%
“…By the end of 2012, 59 out of the 72 endemic countries had completed national mapping surveys [39]. The results of these surveys highlight the marked withincountry geographical heterogeneity [26,[40][41][42][43][44][45][46]. LF mapping is ongoing in the remaining endemic countries except Eritrea, where it has not started yet [2].…”
Section: Introductionmentioning
confidence: 99%
“…15 With regards to LF, available recent reports indicate that in Africa, 34 countries are endemic, and Nigeria is believed to bear the highest burden of LF, with an estimated 80 to 120 million people at risk. [16][17][18] In a recent review article, Adenowo and colleagues 19 noted that schistosomiasis is the second most common neglected tropical disease after hookworm in SubSaharan Africa and accounts for 93% (192 million) of the world estimated 207 million cases of schistosomiasis with the highest prevalence of the infection seen in Nigeria (29 million). Adam and colleagues 20 observed that there is the growing recognition of the importance of developing concise materials and tools to communicate various types of information to policy-makers and those supporting them.…”
Section: Introductionmentioning
confidence: 99%